Gel electrolyte and preparation method and application thereof

By using multi-layer gel electrolyte in zinc ion batteries, combining polymer gel and ionic liquid gel, the leakage of liquid electrolytes and the low conductivity of all-solid electrolytes are solved, and the cycle life and safety performance of the battery are significantly improved.

CN119695301AActive Publication Date: 2025-03-25DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202311254117.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-25
Publication Date
2025-03-25
Estimated Expiration
2043-09-25

AI Technical Summary

Technical Problem

The liquid electrolytes of existing zinc ion batteries have leakage, combustion risks and corrosion problems, while the Zn2+ diffusion kinetics and low ionic conductivity of all solid electrolytes limit their application.

Method used

Using multi-layer gel electrolyte, by combining the polymer gel with an ionic liquid gel coated on its surface, a gel structure with a concentration gradient is formed, which improves the electrode interface contact and ionic conductivity, and inhibits the growth of zinc dendrites.

Benefits of technology

It effectively avoids liquid leakage and the growth of zinc dendrites, improves the cycle life of the battery, and enhances the safety performance and ionic conductivity of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119695301A_ABST
    Figure CN119695301A_ABST
Patent Text Reader

Abstract

The invention discloses a gel electrolyte and a preparation method and application thereof. The gel electrolyte comprises polymer gel and ionic liquid gel coated on the surface of the polymer gel; the polymer is selected from at least one of polyacrylamide, polyvinyl alcohol and polyacrylic acid; the ionic liquid is selected from at least one of acryloyloxyethyl trimethyl ammonium chloride, (3-acrylamidopropyl) trimethyl ammonium chloride, 1-vinyl-3-methylimidazolium trifluoromethanesulfonate and 1-vinyl-3-methylimidazolium tetrafluoroborate, and the ionic liquid is selected from at least one of acryloyloxyethyl trimethyl ammonium chloride and (3-acrylamidopropyl) trimethyl ammonium chloride. Due to the synergistic effect of the ionic liquid and acrylamide, the multi-layer gel electrolyte provided by the invention has relatively high ionic conductivity, the wettability of an electrode-electrolyte interface is good, the growth of zinc dendrites can be effectively hindered, and the cycle life of the battery is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a gel electrolyte and a preparation method and application thereof, belonging to the field of electrolyte materials. Background Art

[0002] Nowadays, the growth of portable electronics, electric vehicles and renewable energy has increased the huge demand for high-performance energy storage devices. Lithium-ion batteries (LIBS) have attracted widespread attention due to their high energy density and energy efficiency. However, due to the limited lithium resources and the use of organic solvents as electrolytes in LIBs, people are concerned about the safety of LIBs. In recent years, rechargeable aqueous zinc-ion batteries (ZIBs) have been considered as the next generation of promising alternative energy storage technology due to their abundant resources, environmental friendliness, low cost and good safety performance.

[0003] Liquid electrolytes face problems such as leakage, combustion risk, and corrosion of organic electrolytes. At the same time, all-solid electrolytes have Zn 2+ Poor diffusion kinetics and low ionic conductivity greatly limit their applications. Summary of the invention

[0004] Hydrogel electrolytes are obtained by mixing zinc salt solutions with a matrix, which can greatly improve electrode interface contact, ionic conductivity, safety performance and other issues. Hydrogels can act as a mechanical barrier and inhibit dendrite growth to a certain extent, alleviating side reactions caused by water. On the other hand, they are often used in flexible wearable batteries due to their adjustable shape, good flexibility, porous structure and good mechanical properties.

[0005] The purpose of the present invention is to provide a multi-level gel electrolyte with a concentration gradient and a preparation method and application thereof. The manufactured multi-level gel electrolyte can effectively avoid liquid leakage and zinc negative electrode dendrite growth.

[0006] According to one aspect of the present application, a gel electrolyte is provided, the gel electrolyte comprising a polymer gel and an ionic liquid gel coated on the surface of the polymer gel;

[0007] The polymer is selected from at least one of polyacrylamide, polyvinyl alcohol and polyacrylic acid;

[0008] The ionic liquid is selected from at least one of acryloyloxyethyl trimethylammonium chloride, (3-acrylamide propyl) trimethylammonium chloride, 1-vinyl-3-methylimidazolium trifluoromethanesulfonate, and 1-vinyl-3-methylimidazolium tetrafluoroborate.

[0009] The thickness of the gel electrolyte is 0.5 mm to 1 mm.

[0010] According to another aspect of the present application, a method for preparing the above-mentioned gel electrolyte is provided, comprising the following steps:

[0011] (1) polymerizing an aqueous solution containing a polymer monomer, a crosslinking agent, and an initiator in a mold to obtain a polymer gel;

[0012] (2) Spraying an ionic liquid aqueous solution, a crosslinking agent aqueous solution and an initiator aqueous solution onto the surface of the polymer gel obtained in (1) in sequence to react and obtain the gel electrolyte.

[0013] The polymer monomer is selected from at least one of acrylamide, vinyl alcohol and acrylic acid;

[0014] The crosslinking agent is selected from at least one of N,N'methylenebisacrylamide, ethylene glycol diacrylate, 1,4-butanediol diacrylate, and ethylene glycol dimethacrylate;

[0015] The initiator is selected from at least one of ammonium persulfate, potassium persulfate, benzoyl oxide, and tert-butyl hydroperoxide.

[0016] In the aqueous solution containing polymer monomers, crosslinking agent and initiator, the mass concentration of the polymer monomers is 50-350 mg / ml;

[0017] The mass ratio of the cross-linking agent to the polymer monomer is 0.002:1 to 0.004:1;

[0018] The mass ratio of the initiator to the polymer monomer is 0.002:1 to 0.004:1.

[0019] The polymerization temperature is 70-80°C;

[0020] The polymerization time is 12 to 24 hours.

[0021] Before the polymerization, nitrogen is introduced into the aqueous solution containing the polymer monomer, the crosslinking agent and the initiator;

[0022] The time for introducing nitrogen is 1 to 10 minutes.

[0023] The mass concentration of the ionic liquid aqueous solution is 100 to 300 mg / ml;

[0024] The volume of the ionic liquid aqueous solution is 1% to 5% of the volume of the aqueous solution containing the polymer monomer, the crosslinking agent, and the initiator;

[0025] The mass concentration of the cross-linking agent aqueous solution is 2 to 6 mg / ml;

[0026] The volume of the crosslinking agent aqueous solution is 1% to 5% of the volume of the aqueous solution containing the polymer monomer, the crosslinking agent, and the initiator;

[0027] The mass concentration of the initiator aqueous solution is 2 to 6 mg / ml;

[0028] The volume of the initiator aqueous solution is 1% to 5% of the volume of the aqueous solution containing the polymer monomer, the crosslinking agent and the initiator.

[0029] The reaction time is 12 to 24 hours;

[0030] The reaction temperature is 70-80°C.

[0031] According to another aspect of the present application, an aqueous zinc ion battery is provided, wherein the aqueous zinc ion battery contains the above-mentioned gel electrolyte.

[0032] Due to the synergistic effect of the ionic liquid and acrylamide, the multilayer gel electrolyte proposed in the present invention has higher ionic conductivity, good wettability of the electrode-electrolyte interface, and can effectively hinder the growth of zinc dendrites, thereby improving the cycle life of the battery.

[0033] The beneficial effects of this application include:

[0034] (1) The preparation method of the multi-level gel electrolyte with concentration gradient proposed by the present invention is simple, environmentally friendly, low-cost and has good safety performance;

[0035] (2) Since the surface is sprayed with an ionic liquid gel electrolyte with a concentration gradient, and since it has the characteristics of both ionic liquid and polymer network, its polymer molecular chains are interconnected or entangled to form a spatial network structure, and the structural gaps are filled with anions and cations as the dispersion medium, so the ionic gel has high ionic conductivity;

[0036] (3) The multi-layered gel electrolyte with a concentration gradient proposed in the present invention avoids the concentration polarization caused by anion migration during the cycle, and Zn 2+ It can be uniformly deposited / stripped on the surface without generating zinc dendrites, which significantly enhances the cycle life of aqueous zinc-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 Symmetrical cycling curve of a symmetric battery assembled with a multi-level gel electrolyte with concentration gradient prepared in Example 1.

[0038] Figure 2 This is the SEM image of the zinc plate of the symmetrical battery with multi-level gel electrolyte with concentration gradient prepared in Example 1 after 100 cycles, with a scale of 1 μm.

[0039] Figure 3 Coulombic efficiency diagram of Zn / Cu assembled with multi-level gel electrolyte with concentration gradient prepared in Example 1.

[0040] Figure 4 The rate diagram of the symmetrical battery assembled with a multi-level gel electrolyte with concentration gradient prepared in Example 1 at different current densities.

[0041] Figure 5 The voltage-current curve of the Zn / Ti battery assembled with a multi-level gel electrolyte with a concentration gradient prepared in Example 1. DETAILED DESCRIPTION

[0042] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.

[0043] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.

[0044] Embodiment 1:

[0045] (1) at 25° C., 7 g of acrylamide was completely dissolved in 42 mL of deionized water, and then 0.021 g of N,N'-methylenebisacrylamide and 0.021 g of ammonium persulfate were added in sequence until the mixture was completely dissolved to obtain an acrylamide mixed solution;

[0046] (2) introducing nitrogen into the acrylamide mixed solution prepared in (1) and pouring it into a mold for heating and polymerization at 70° C. to 80° C. for 12 hours;

[0047] (3) 0.4 g of acryloyloxyethyl trimethyl ammonium chloride was completely dissolved in 2 mL of deionized water, and then 0.008 g of N,N'-methylenebisacrylamide was added and completely dissolved, and then sprayed onto the surface of the polyacrylamide gel prepared in (2) using a spray gun;

[0048] (4) After (3) was allowed to stand for 2 hours, 0.008 g of ammonium persulfate was completely dissolved in 2 mL of deionized water and sprayed onto the surface of the gel after standing using a spray gun;

[0049] (5) The gel prepared in (4) is heated and polymerized at 70° C. to 80° C. for 12 hours to obtain a multi-level gel electrolyte with a concentration gradient.

[0050] Figure 1 The symmetrical cycle curve of the symmetrical battery assembled with a multi-level gel electrolyte with a concentration gradient prepared in Example 1 shows that the voltage polarization is small and stable during the cycle.

[0051] Figure 2This is a SEM image of the zinc plate after 100 cycles of the symmetrical battery with multi-level gel electrolyte with concentration gradient prepared in Example 1, with a scale of 1 μm. The surface of the zinc plate after the cycle is flat and the dendrite growth is less.

[0052] Figure 3 This is the coulombic efficiency diagram of the Zn / Cu assembled with a multi-level gel electrolyte with a concentration gradient prepared in Example 1. The coulombic efficiency remains stable after 350 cycles.

[0053] Figure 4 The rate diagrams of the symmetrical battery assembled with a multi-level gel electrolyte with a concentration gradient prepared in Example 1 at different current densities confirm that the gel electrolyte proposed in the present invention has broad application prospects.

[0054] Figure 5 The voltage-current curve of the Zn / Ti battery assembled with a multi-level gel electrolyte with a concentration gradient prepared in Example 1.

[0055] Embodiment 2:

[0056] (1) At 25° C., 3 g of acrylamide was completely dissolved in 36 mL of deionized water, and then 0.009 g of N,N'-methylenebisacrylamide and 0.009 g of ammonium persulfate were added in sequence until the mixture was completely dissolved to obtain an acrylamide mixed solution;

[0057] (2) introducing nitrogen into the acrylamide mixed solution prepared in (1) and pouring it into a mold for heating and polymerization at 70° C. to 80° C. for 12 hours;

[0058] (3) 0.4 g of acryloyloxyethyl trimethyl ammonium chloride was completely dissolved in 2 mL of deionized water, and then 0.008 g of N,N'-methylenebisacrylamide was added and completely dissolved, and then sprayed onto the surface of the polyacrylamide gel prepared in (2) using a spray gun;

[0059] (4) After (3) was allowed to stand for 2 hours, 0.008 g of ammonium persulfate was completely dissolved in 2 mL of deionized water and sprayed onto the surface of the gel after standing using a spray gun;

[0060] (5) The gel prepared in (4) is heated and polymerized at 70° C. to 80° C. for 12 hours to obtain a multi-level gel electrolyte with a concentration gradient.

[0061] Embodiment 3:

[0062] (1) At 25° C., 14 g of acrylamide was completely dissolved in 42 mL of deionized water, and then 0.042 g of N,N'-methylenebisacrylamide and 0.042 g of ammonium persulfate were added in sequence until the mixture was completely dissolved to obtain an acrylamide mixed solution;

[0063] (2) introducing nitrogen into the acrylamide mixed solution prepared in (1) and pouring it into a mold for heating and polymerization at 70° C. to 80° C. for 12 hours;

[0064] (3) 0.4 g of acryloyloxyethyl trimethyl ammonium chloride was completely dissolved in 2 mL of deionized water, and then 0.008 g of N,N'-methylenebisacrylamide was added and completely dissolved, and then sprayed onto the surface of the polyacrylamide gel prepared in (2) using a spray gun;

[0065] (4) After (3) was allowed to stand for 2 hours, 0.008 g of ammonium persulfate was completely dissolved in 2 mL of deionized water and sprayed onto the surface of the gel after standing using a spray gun;

[0066] (5) The gel prepared in (4) is heated and polymerized at 70° C. to 80° C. for 12 hours to obtain a multi-level gel electrolyte with a concentration gradient.

[0067] Embodiment 4:

[0068] (1) at 25° C., 7 g of acrylamide was completely dissolved in 42 mL of deionized water, and then 0.021 g of N,N'-methylenebisacrylamide and 0.021 g of ammonium persulfate were added in sequence until the mixture was completely dissolved to obtain an acrylamide mixed solution;

[0069] (2) introducing nitrogen into the acrylamide mixed solution prepared in (1) and pouring it into a mold for heating and polymerization at 70° C. to 80° C. for 12 hours;

[0070] (3) 0.2 g of acryloyloxyethyl trimethyl ammonium chloride was completely dissolved in 2 mL of deionized water, and then 0.004 g of N, N'-methylene bisacrylamide was added and completely dissolved, and then sprayed onto the surface of the polyacrylamide gel prepared in (2) using a spray gun;

[0071] (4) After (3) was allowed to stand for 2 hours, 0.004 g of ammonium persulfate was completely dissolved in 2 mL of deionized water and sprayed onto the surface of the gel after standing using a spray gun;

[0072] (5) The gel prepared in (4) is heated and polymerized at 70° C. to 80° C. for 12 hours to obtain a multi-level gel electrolyte with a concentration gradient.

[0073] Embodiment 5:

[0074] (1) at 25° C., 7 g of acrylamide was completely dissolved in 42 mL of deionized water, and then 0.021 g of N,N'-methylenebisacrylamide and 0.021 g of ammonium persulfate were added in sequence until the mixture was completely dissolved to obtain an acrylamide mixed solution;

[0075] (2) introducing nitrogen into the acrylamide mixed solution prepared in (1) and pouring it into a mold for heating and polymerization at 70° C. to 80° C. for 12 hours;

[0076] (3) 0.6 g of acryloyloxyethyl trimethyl ammonium chloride was completely dissolved in 2 mL of deionized water, and then 0.012 g of N, N'-methylene bisacrylamide was added and completely dissolved, and then sprayed onto the surface of the polyacrylamide gel prepared in (2) using a spray gun;

[0077] (4) After (3) was allowed to stand for 2 hours, 0.012 g of ammonium persulfate was completely dissolved in 2 mL of deionized water and sprayed onto the surface of the gel after standing using a spray gun;

[0078] (5) The gel prepared in (4) is heated and polymerized at 70° C. to 80° C. for 12 hours to obtain a multi-level gel electrolyte with a concentration gradient.

[0079] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A gel electrolyte, characterized in that: The gel electrolyte comprises a polymer gel and an ionic liquid gel coated on the surface of the polymer gel; The polymer is selected from at least one of polyacrylamide, polyvinyl alcohol and polyacrylic acid; The ionic liquid is selected from at least one of acryloyloxyethyl trimethylammonium chloride, (3-acrylamide propyl) trimethylammonium chloride, 1-vinyl-3-methylimidazolium trifluoromethanesulfonate, and 1-vinyl-3-methylimidazolium tetrafluoroborate.

2. The gel electrolyte according to claim 1, characterized in that The thickness of the gel electrolyte is 0.5 mm to 1 mm.

3. A method for preparing a gel electrolyte according to any one of claims 1 or 2, characterized in that: The following steps are involved: (1) polymerizing an aqueous solution containing a polymer monomer, a crosslinking agent, and an initiator to obtain a polymer gel; (2) Spraying an ionic liquid aqueous solution, a crosslinking agent aqueous solution and an initiator aqueous solution onto the surface of the polymer gel obtained in (1) in sequence to react and obtain the gel electrolyte.

4. The preparation method according to claim 3, characterized in that: The polymer monomer is selected from at least one of acrylamide, vinyl alcohol and acrylic acid; The crosslinking agent is selected from at least one of N,N'methylenebisacrylamide, ethylene glycol diacrylate, 1,4-butanediol diacrylate, and ethylene glycol dimethacrylate; The initiator is selected from at least one of ammonium persulfate, potassium persulfate, benzoyl oxide, and tert-butyl hydroperoxide.

5. The preparation method according to claim 3, characterized in that: In the aqueous solution containing polymer monomers, crosslinking agent and initiator, the mass concentration of the polymer monomers is 50-350 mg / ml; The mass ratio of the cross-linking agent to the polymer monomer is 0.002:1 to 0.004:1; The mass ratio of the initiator to the polymer monomer is 0.002:1 to 0.004:

1.

6. The preparation method according to claim 3, characterized in that: The polymerization temperature is 70-80°C; The polymerization time is 12 to 24 hours.

7. The preparation method according to claim 3, characterized in that: Before the polymerization, nitrogen is introduced into the aqueous solution containing the polymer monomer, the crosslinking agent and the initiator; The time for introducing nitrogen is 1 to 10 minutes.

8. The preparation method according to claim 3, characterized in that: The mass concentration of the ionic liquid aqueous solution is 100 to 300 mg / ml; The volume of the ionic liquid aqueous solution is 1% to 5% of the volume of the aqueous solution containing the polymer monomer, the crosslinking agent, and the initiator; The mass concentration of the cross-linking agent aqueous solution is 2 to 6 mg / ml; The volume of the crosslinking agent aqueous solution is 1% to 5% of the volume of the aqueous solution containing the polymer monomer, the crosslinking agent, and the initiator; The mass concentration of the initiator aqueous solution is 2 to 6 mg / ml; The volume of the initiator aqueous solution is 1% to 5% of the volume of the aqueous solution containing the polymer monomer, the crosslinking agent and the initiator.

9. The preparation method according to claim 3, characterized in that: The reaction time is 12 to 24 hours; The reaction temperature is 70-80°C.

10. An aqueous zinc ion battery, characterized in that: The aqueous zinc ion battery contains the gel electrolyte according to any one of claims 1 or 2.

Citation Information

Patent Citations

  • Method for preparing polymer electrolyte of flexible lithium-ion battery in situ and application

    CN107658500A

  • Method for preparing integrated quasi-solid zinc ion battery

    CN110444822A

  • Multifunctional gel polymer electrolyte and preparation method thereof

    CN115894788A

  • Ionic gel solid electrolyte material and preparation method and application thereof

    CN116741547A

  • Multi-layer structure polymer solid electrolylte and all solid-state battery comprising the same

    US20200235427A1